SARS-CoV-2 infection in female sex workers from Nairobi, Kenya early in the COVID-19 pandemic: Seroincidence and behavioural associations - Su D. Yang; Freda Qi; Karen Colwill; Anne-Claude Gingras; Tara S. Beattie; Joshua Kimani; Rupert Kaul (PLoS ONE, 2026)
While COVID-19 mortality was relatively low in many Sub-Saharan African countries during the first wave of the pandemic, SARS-CoV-2 transmission was extensive. We hypothesized that female sex workers (FSWs) would be at enhanced risk of acquisition of this novel respiratory viral infection, due to intimate contact with multiple sexual partners and solicitation of clients in crowded venues. Here we describe the seroincidence, socio-behavioural associations and clinical outcomes of SARS-CoV-2 infection in Kenyan FSWs early in the pandemic. A longitudinal cohort of 1003 FSWs (257 living with HIV) from Nairobi, Kenya was enrolled in mid-2019, just prior to the pandemic, and plasma was available for SARS-CoV-2 serology from 827 participants at clinical follow up approximately one year later. Socio-behavioural and respiratory symptom data were collected by questionnaire. We examined the association of SARS-CoV-2 infection with socio-behavioural factors. Follow-up was a median of 201 days (range; 92−342 days) after the declaration of the COVID-19 pandemic in Kenya, and 229 (27.7%) participants were SARS-CoV-2 seropositive. Seroprevalence increased steadily with time from pandemic declaration. Infection was not associated with behavioural or demographic parameters but was strongly associated with time since start of the pandemic (p < 0.0001). Respiratory symptoms during the past 6 months were reported by almost two-thirds of participants (510/821; 62.1%), with SARS-CoV-2 infection specifically associated with self-reported difficulty breathing, dizziness, fever, loss of smell, myalgia, rhinorrhea, and odynophagia; approximately half of the cases were completely asymptomatic. HIV status was not associated with differences in SARS-CoV-2 seroincidence or symptoms, and no behavioural or sociodemographic associations of infection were apparent. Pre-pandemic serology demonstrated antibodies recognizing one of SARS-CoV-2 Spike, RBD, or N in 151/994 participants (15.2%), but these were not associated with protection against subsequent SARS-CoV-2 infection. Overall, SARS-CoV-2 seroincidence was high early in the pandemic among Nairobi-based FSWs, with no clear socio-behavioural associations of infection.